Online optimal stationary reference frame controller for inverter interfaced distributed generation in a microgrid system - Xiao-yan Jiang; Chuan He; Kittisak Jermsittiparsert (Energy Reports, 2020)
This paper presents a novel optimal real-time controller for inverter-based distributed generation units in an islanded microgrid. With respect to the fact that the microgrid has a completely nonlinear structure and its dynamics is constantly changing, the linear controllers with constant and inflexible coefficients cannot maintain proper response in a wide range of operation conditions. Hence, an optimal nonlinear controller that theirs coefficient are adjusted in a real-time manner based on fuzzy logic is presented. To improve the performance of the proposed real-time controller, its fuzzy system parameters are determined using an offline particle swarm optimization algorithm for various operation conditions. In the proposed real-time controller, proportional-resonant controllers are used due to their advantage in the stationary reference frame for controlling the voltage and current of distributed generation units in the microgrid. Capability and efficiency of the proposed real-time controller are evaluated in different operation scenarios in MATLAB/Simulink environment. The simulation results shows that changing the control coefficients online with respect to operation condition leads to achievement of an optimum answer for voltage during the occurrence of islanding condition and also in case of load variation in the islanded microgrid.
Keywords: 330; Microgrid; Distributed generation; Proportional-resonant controller; Fuzzy logic; Particle swarm optimization (PSO) algorithm